Comparative Efficacy of Vedolizumab and Adalimumab in Ulcerative Colitis Patients Previously Treated With Infliximab. Issue 11 (1st April 2019) - Favale, Agnese; Onali, Sara; Caprioli, Flavio; Pugliese, Daniela; Armuzzi, Alessandro; Macaluso, Fabio Salvatore; Orlando, Ambrogio; Viola, Anna; Fries, Walter; Rispo, Antonio; Castiglione, Fabiana; Mocci, Giammarco; et al.
Abstract: Background: Adalimumab (ADA) and vedolizumab (VDZ) have shown efficacy in moderate to severe ulcerative colitis (UC) patients who failed infliximab (IFX). Although, a comparative efficacy evaluation of ADA and VDZ in this clinical setting is currently missing. Aim: The aim of this study is to compare the efficacy of ADA and VDZ in patients affected by UC who failed IFX. Methods: Clinical records of UC patients from 8 Italian IBD referral centers who failed IFX and were candidates to receive either ADA or VDZ were retrospectively reviewed. The primary end point was therapeutic failure at week 52. Secondary end points included therapy discontinuation at weeks 8, 24 and 52, the discontinuation-free survival, and safety. Results: One hundred sixty-one UC patients, 15 (9.2%) primary, 83 (51.6%) secondary IFX failures, and 63 (39.2%) IFX intolerants were included. Sixty-four (40%) patients received ADA and 97 (60%) VDZ as second line therapy. At week 52, 37.5% and 28.9% of patients on ADA and VDZ, respectively, had therapeutic failure ( P = 0.302). However, the failure rate was significantly higher in the ADA group as compared with VDZ group among IFX secondary failures (48.0% ADA vs 22.4%VDZ, P = 0.035). The therapy discontinuation-free survival was significantly higher in the group of IFX secondary failures who received VDZ as compared with ADA at both the univariate ( P = 0.007) and multivariate survival analysis (OR 2.79; 95% CI, 1.23–6.34; P = 0.014). No difference in the failure and biologic discontinuation-free survival was observed in the IFX primary failure and intolerant subgroups. Conclusion: Vedolizumab might be the therapy of choice in those UC patients who showed secondary failure to IFX. Video Abstract: Abstract : In a retrospective cohort of ulcerative colitis patients who failed Infliximab, Vedolizumab was more effective than Adalimumab among secondary failures while they were equally effective among Infliximab intolerants.